Discovery of Research Gaps in Game Learning Analytics Applications on Learning Processes - Silva, Gabriel; Rodrigues, Rodrigo Lins; Campos Filho, Amadeu Sá; Amorim, Américo (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2020)
The benefits of game applications in the field of education have been increasingly evident due to the use of Game Learning Analytics, which is the collection, analysis and extraction of information from data obtained through Serious Games. In this article, this article aims to carry out a systematic mapping in order to identify research gaps in studies that use Game Learning Analytics to analyze an educational process, analyzing the observed educational phenomenon, the algorithms or techniques used and the characteristics and number of participants. We understand that even though the Game Learning Analytics area is still very new, it has enormous potential in helping what we value most, teaching.